Exploring student voice for learner-driven learning / Gurnam Kaur Sidhu, Lim Peck Choo and Chan Yuen Fook - Sidhu, Gurnam Kaur; Lim, Peck Choo; Chan, Yuen Fook (UiTM Press, 2017)
Current pedagogy has witnessed a paradigm shift towards a more learnercentred approach where the individual learner is the focus of teaching rather than the body of knowledge. As principles guiding learner-centred learning become more defined, therein lays a critical call to take heed of student voice for more effective delivery systems and teacher growth. Therefore, this paper explored student voice regarding the implementation of an English Language course offered to students under the Mengubah Destini Anak Bangsa (MDAB) programme in UiTM, Malaysia. The study involved 341 pre-diploma students from three UiTM branch campuses. Data were collected using a questionnaire and nine focus group interviews. Findings revealed that students held rather positive and favourable views towards the implementation of the program with regards to lecturer preparation, language use, lesson presentation, classroom management and classroom atmosphere. Inferential statistics revealed that there was no significant difference in the students' perceptions with regards to gender and discipline of study but a significant difference was seen with regards to language proficiency and campus locality. Students also highlighted concerns regarding student language proficiency, contact hours, the course curriculum, assignments, teaching staff and learning within a homogenous group. Students called for a more learner-driven curriculum that would address their needs and build upon their knowledge and skills. So that they could become more holistic and confident tertiary students. The findings implied that student voice cannot be ignored as it has a role for effective feedback and learner-driven learning.